2022
DOI: 10.1021/acsmacrolett.2c00040
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity Enhancement of Polymer Electrolytes by Directed Crystallization

Abstract: We report that hot stretching of poly­(ethylene oxide) (PEO)-based solid polymer electrolytes (SPEs) can lead to a preferred orientation of PEO crystalline lamellae, thereby reducing the tortuosity of the ion-conduction pathway along the thickness direction of the SPE film, causing improved ionic conductivity. The hot stretching method is implemented by stretching SPE films above the melting point of PEO in an inert environment followed by crystallization at room temperature while maintaining the applied strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…In this work, complexed-membrane of MC/CMC (80/20) + 10 % LiClO 4 has lower crystallinity index than blend membrane of MC/CMC (80/20) cause complexed-membrane of MC/CMC (80/20) + 10 % LiClO 4 has higher ionic conductivity than blend membrane of MC/CMC (80/20). It agrees with some previous research such as, [71,72] where the amorphous phase increases ionic conductivity as lithium salt consequence which disrupts the crystallinity. [73] Thermal analysis of biopolymer electrolyte membrane Thermal stability is important in battery cell to prevent overheating, which is probably caused by overcharging.…”
Section: Mechanical and Crystallinities Analysis Of Biopolymer Electr...supporting
confidence: 93%
“…In this work, complexed-membrane of MC/CMC (80/20) + 10 % LiClO 4 has lower crystallinity index than blend membrane of MC/CMC (80/20) cause complexed-membrane of MC/CMC (80/20) + 10 % LiClO 4 has higher ionic conductivity than blend membrane of MC/CMC (80/20). It agrees with some previous research such as, [71,72] where the amorphous phase increases ionic conductivity as lithium salt consequence which disrupts the crystallinity. [73] Thermal analysis of biopolymer electrolyte membrane Thermal stability is important in battery cell to prevent overheating, which is probably caused by overcharging.…”
Section: Mechanical and Crystallinities Analysis Of Biopolymer Electr...supporting
confidence: 93%
“…This result shows that Li + directly interacts with the tail, pinning it to the interface, in a manner that is analogous to previously reported H-bonding interactions at air/aqueous interfaces decorated with ODMS-MIM + . The binding of Li + to the tail parallels the interactions found in solutions, , polymers, battery materials, and small molecules , where solvation and pairing interactions of the Li + cation by oxygen moieties were found. Similarly, recent work has shown how contact ion pairs are preferable in Li + binding to sulfate headgroups, yet they possess weak thermodynamic binding affinities relative to larger cations .…”
supporting
confidence: 85%
“…Liu et al reported a hot drawing technique by which crystalline sheets perpendicular to the drawing direction were selected, and the crystallinity of the electrolyte was reduced. As shown in Figure 3 a, this enhanced ionic conductivity in the through-plane direction of the SPE films by reducing the ionic conduction pathway [ 49 ]. Liang et al combined the zirconia skeleton (ZrO 2 @ILs) with the vertical channel of fast Li ion movement generated by hydrolysis in situ with PEO to enhance the conductivity and mechanical properties of electrolyte ions, as shown in Figure 3 b.…”
Section: Polymer Electrolytesmentioning
confidence: 99%
“… ( a ) Schematic diagram of different electrolyte lamellar orientations and lithium-ion transport pathways (Reprinted with permission from [ 49 ]; Copyright 2022, ACS Macro Letters); ( b ) PEO polymer with ZrO 2 @ILs vertical channel design to improve mechanical strength and ionic conductivity (Reprinted with permission from [ 50 ]; Copyright 2021, ACS Applied Materials & Interfaces). ( c ) Schematic diagram of polysulfide and lithium-ion transport by graphene-coated PP diaphragm (Reprinted with permission from [ 53 ]; Copyright 2018, ACS Applied Materials & Interfaces).…”
Section: Figurementioning
confidence: 99%